The Development of Teaching Materials Based on Context and Creativity to Increase Students Scientific Literacy - Rahmani, Rahmani; Mustadi, Ali; Maulidar, Maulidar; Senen, Anwar (SCAD Independent, 2021)
This research aimed to develop context-based teaching materials and creativity to improve elementary school students' scientific literacy in the material of human and animal motion organs. The research method used in this research is Research and Development (Research and Development) which includes stage 1) Preliminary studies in the form of literature studies, 2) Study of teaching material development and 3) limited trials using a one-shot case study. The results of the analysis of the data from the questionnaire assessment of teaching materials by material experts showed that the aspect of content eligibility was 90%, the feasibility aspect was 78% presentation, the aspect of language eligibility was 83% and the aspect assessment was context and creativity 92%. The results of the questionnaire data analysis of teaching material assessment by media experts showed that the size of teaching materials was 69%, the cover was 86% and the content design was 85. Therefore, the teacher's response to context-based teaching materials using questionnaire sheets, and the response obtained that using teaching materials can facilitate teachers to learn science in a simple but meaningful way.